Are there any Differences between Chemical Element Contents of Goitrous and Adenomatous Thyroid? - Zaichick, Vladimir (Jour Med Resh and Health Sci, 2021)
Background: Thyroid benign nodules (TBNs) are the most common lesions of this endocrine gland and are prevalent diseases around the world. Among TBNs the colloid goiter (CG) and thyroid adenoma (TA) are very frequent diseases. An evaluation of the variant of TBNs is clinically important for subsequent therapeutic interventions, as well as for more clear understanding the etiology of these disorders. Objectives: The aim of this exploratory study was to examine differences in the content of aluminum (Al), boron (B), barium (Ba), bromine (Br), calcium (Ca), chlorine (Cl), coper (Cu), iron (Fe), I, potassium (K), lithium (Li), magnesium (Mg), manganese (Mn), sodium (Na), phosphorus (P), sulfur (S), silicon (Si), strontium (Sr), vanadium (V), and zinc (Zn) in tissues of CG and TA. Methods: Thyroid tissue levels of twenty chemical elements (ChE) were prospectively evaluated in 46 patients with CG and 19 patients with TA. Measurements were performed using a combination of non-destructive and destructive methods: instrumental neutron activation analysis with high resolution spectrometry of short-lived radionuclides (INAA-SLR) and inductively coupled plasma atomic emission spectrometry (ICP-AES), respectively. Tissue samples were divided into two portions. One was used for morphological study while the other was intended for ChE analysis. Results: It was observed that in both CG and TA tissues contents of Al, B, Br, Cl, Cu, Na, and Zn increased, content of I decreased, whereas levels of Ba, Ca, K, and Sr did not changed in comparison with normal thyroid tissue. It was not found any differences between ChE contents of CG and TA, with the exception of Br and Mg. The Br level in TA tissue was almost 11 times higher, while the Mg content was 1.5 times lower than in CG tissue. Conclusions: From obtained results it was possible to conclude that the common characteristics of CG and TA tissue samples were elevated level of Al, B, Br, Cl, Cu, Na, and Zn and reduced level of I in comparison with normal thyroid and, therefore, these ChE can be involved in etiology and pathogenesis of such thyroid disorders as CG and TA